Impact of Teaching and Learning Using the Professional Learning Community through the CSIPL Process - Theerapat Sinthudech; Wannatida Yonwilad (Journal of Educational Issues, 2024)
This research aims to 1) study activities that affected the success of the PLC process, 2) study the CSIPL-based learning management process, and 3) study the expression behaviors that provided opportunities to develop learning management based on the CSIPL process. The instruments in this study were: (1) The CSIPL learning management activity plan, which includes five activities: 1) Create a story, 2) Set rules, 3) Insert content, 4) Participate in the game, and 5) Lesson learned. (2) Behavior activities in the CSIPL form include: 1) puzzle letters; 2) haunted pianos; 3) lost eyes; 4) whispers; 5) The Book of Mantra, 6) puzzle sounds; 7) death messages; 8) believing I’m dead; 9) ghosts without voices, and 10) final codes. (3) PLC process assessment form. The data were analyzed using frequency, percentages, mean score (M), standard deviation (SD), and thematic analysis. This research shows that 1) collaboration and shared visions are the stationary driving forces, accounting for 10% of equal work values, while a high collective focus on student learning (45%) drives PLC processes. 2) CSIPL process averaged 4.03 with a standard deviation of 0.74 which shows the suitability of appropriateness at a high level. 3) The overall earnings management for the CSIPL process is 4.22, which means that the level of suitability is high. 4) Students lack the experience of learning what they receive from activities that reflect process control because teachers lack the expertise, they have achieved following the PLC process.